Persepsi Intonasi Tuturan Kaum Bangsawan Melayu Terhadap Emosi (Perception of the Speech Intonation of the Malay Nobility Against Emotions) - Emmy Erwina (Jurusan Tadris Bahasa Indonesia, 2021)
This study aims to describe the intonation perception of the Malay aristocrats' speech on emotions. This study uses an experimental phonetic study among the nobility in Tanjungpura, Langkat Regency, North Sumatra. This study uses acoustic-phonetic theory and also uses the Praat program. Data analysis used the Average method so that the percentage of Malay nobility's perception of the intonation of emotional speech was obtained. The results of this study get the percentage of data on angry emotional speech, which is 40%. For the percentage of data on the perception of the nobility towards sad emotional speech, namely all respondents.Penelitian ini bertujuan untuk mendeskripsikan persepsi intonasi tuturan kaum bangsawan Melayu terhadap emosi. Penelitian ini menggunakan kajian fonetik eksperimental pada kalangan bangsawan di Tanjungpura, Kabupaten Langkat, Sumatera Utara. Penelitian ini menggunakan teori fonetik akustik serta digunakan juga program Praat. Analisis data menggunakan metode Average sehingga diperoleh persentase persepsi kaum bangsawan Melayu terhadap intonasi tuturan emosi. Hasil dari penelitian ini mendapatkan persentase data terhadap tuturan emosi marah, yaitu sebesar 40%. Untuk persentase data persepsi kaum bangsawan terhadap tuturan emosi sedih yaitu seluruh responden.Â